2019
DOI: 10.3390/lubricants7030021
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Elements of Secondary Structures on the Wear Resistance of Steel in Friction against Experimental Aluminum Alloys for Monometallic Journal Bearings

Abstract: This article describes the elemental composition of secondary structures formed on the steel contact surface during wear test against experimental Al alloys. Wear tests were carried out according to the rotating steel roller-fixed shoe of an antifriction alloy scheme under boundary lubrication conditions. The duration of the test was 40 h, and motor oil M14V2 was used as a lubricant. The microstructure and elemental characterization of the steel surface before and after the tribological test was obtained by sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Moreover, Mo with its ability to form MoS 2 on the friction surface under lubricated conditions is a favorable additive in obtaining secondary structures. Besides, a previous study has shown that the presence of Mo and Cr acted as a favorable effect on the wear resistance of steel and the friction coefficient of the rubbing surfaces due to the formation of secondary structures with optimal composition [13]. However, the question about the desirability of using these metals in Al-based alloys is multifaceted and complex, and will be considered following a further detailed investigation of the mechanical and tribological behavior of obtained alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Mo with its ability to form MoS 2 on the friction surface under lubricated conditions is a favorable additive in obtaining secondary structures. Besides, a previous study has shown that the presence of Mo and Cr acted as a favorable effect on the wear resistance of steel and the friction coefficient of the rubbing surfaces due to the formation of secondary structures with optimal composition [13]. However, the question about the desirability of using these metals in Al-based alloys is multifaceted and complex, and will be considered following a further detailed investigation of the mechanical and tribological behavior of obtained alloys.…”
Section: Introductionmentioning
confidence: 99%
“…This paper continues the studies of new antifriction aluminum alloys beginning in [1][2][3][4][5][6][7][8]. Previously, the authors investigated compositions, mechanical and tribological properties of the new antifriction aluminum alloys.…”
Section: Introductionmentioning
confidence: 69%
“…The tests were carried out in the API CB oil. Details of the test procedures are described in [1][2][3]. The shoes were made of antifriction aluminum alloys.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is a part of an ongoing research aimed at replacing bronzes with aluminum-based alloys [49][50][51]. The goal of the work is to reveal typical processes taking place on the surface of antifriction aluminum alloys during friction.…”
Section: Introductionmentioning
confidence: 99%